Thailand's Provincial Electricity Authority (PEA) electronic customer relationship - Choknumkij, Karn; Fongsuwan, Wanno (My University, 2014)
This study is an analysis of Thailand's Provincial Electricity Authority's (PEA) use of Electronic Customer Resource Management (CRM) systems and how they affect PEA's customers. The PEA operates as a government enterprise in the utility sector, having primary responsibilities which include power generation, procurement, distribution and sale of electricity to the public, businesses and the industrial sector. This currently includes 99.4% of Thailand, with a total of 74 of 77 provinces covering an area of 510,000 km2. Research methodologies used within this study include both quantitative and qualitative research. Quantitative is further qualified by the use of a survey given to 500 PEA executives. The Partial Least Square (PLS) technique, a form of structural equation modeling, is additionally used due to it being component-based rather t h an covariance-based. Additionally, qualitative research is supported by input from questionnaires from 10 key Thai PEA officials utilizing the purposive sampling approach. The results showed that two factors had an immediate and positive impact on customer satisfaction: There were Service Quality and E-CRM. Furthermore, there was also an immediate and positive impact on PEA Customer Satisfaction. A fact recognized by a hypothesis significance p≤0.01, respectively, with the results of qualitative research being consistent with the results of quantitative research. So, if the PEA has a good ECRM and Service Quality, organizational performance increases.
Keywords: Customer satisfaction; Electronic customer relationship managemen; Service quality